Development of integrated impedance and mass sensing biosensor - Siddiquei, Md Hasin Reza (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
Cell culture is essential to diagnose many life threatening diseases like cancer, HIV, hepatitis B etc. Mass change of biological cells is detected by Quartz Crystal Microbalance (QCM)-based mass-sensor through a shift in its resonance frequency, whereas in impedance-sensing it is correlated with the change of cell impedance. Both of these techniques are individually able to provide simple interface for real time monitoring the population rate and electrical activity of the living cells in cell culture media. Mass-sensing technique is more reliable than impedance-sensing technique but it is less sensitive especially for floating cells in the culture medium. On the other hand, the accuracy of the impedance-sensing technique is affected by some external parameters such as temperature, magnetic field etc. A new biosensor system that has combined simultaneously both the mass-sensing as well as impedance-sensing systems together, is presented in this thesis. So that one system's above mentioned disadvantages can be compensated by the other system, as a result a more efficient system would be possible. A prototype of the proposed system that combines both impedance and mass-sensing has been characterized and used to monitor the Michigan Cancer Foundation-7 (MCF-7) breast cancer cell culture. The mass variations and electrical properties of the MCF-7 cell have been successfully characterized by the proposed system. The system showed better performance to measure the population rate for monitoring the electrical activities of the cultured MCF-7 cell over a long period of time. The proposed system would be useful for monitoring the activities of the other biological cells too. It may be an effective and advance solution for monitoring the activities of that cell, where the mass-sensing or impedance-sensing method alone has limited accuracy when used independently.